Robust topology optimization for structures under interval uncertainty. (September 2016) - Wu, Jinglai; Gao, Jie; Luo, Zhen; Brown, Terry
Highlights: A new non-probabilistic robust topology optimization (RTO) is proposed under interval uncertainty. Interval arithmetic is applied to eliminate the nested double-loop optimization that is highly cost. A Chebyshev interval inclusion function is developed to implement the interval arithmetic. A new design sensitivity analysis approach is developed for the interval objective function. Abstract: This paper proposes a new non-probabilistic robust topology optimization approach for structures under interval uncertainty, as a complementarity of the probabilistic robust topology optimization methods. Firstly, to avoid the nested double-loop optimization procedure that is time consuming in computations, the interval arithmetic is introduced to estimate the bounds of the interval objective function and formulate the design problem under the worst scenario. Secondly, a type of non-intrusive method using the Chebyshev interval inclusion function is established to implement the interval arithmetic. Finally, a new sensitivity analysis method is developed to evaluate the design sensitivities for objective functions like structural mean compliance with respect to interval uncertainty. It can overcome the difficulty due to non-differentiability of intervals and enable the direct application of gradient-based optimization algorithms, e.g. the Method of Moving Asymptotes (MMA), to the interval uncertain topology optimization problems. Several examples are used to demonstrate the effectiveness of the proposed method.